PETA SITUASI DUSUN BABADAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN JAWA TENGAH - , VERINDA SEPTITA N ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The practical lecturing work was done in Babadan, Beluk village, Babadan district in Klaten regency, central Java province. The objective of this work was to determine students' skills in using tools and skills in measurement. The practice was conducted in order to measure students ability in applying the materials they already after all lectures. The activity conducted during the practical lecturing work was measuring an area then mapped it. The measurement was done by polygon method. The measurement covered KKH, KKV and detail. After the measurement had finished, it was continued by making situation map of the area. The measurement gave result in the form of angle and distance data for the polygon and coordinate for details. The result of this practical work is situation map in 1:500 scale in forms of hard ans doft copies. The hard copy was printed on A1 paper and the soft copy was submitted in the compact disc (CD).